10-year evaluation of the cementless low-contact- stress rotating-platform total knee arthroplasty. - Efstathopoulos, Nikolaos; Mavrogenis, Andreas F; Lallos, Stergios; Nikolaou, Vassilios; Papagelopoulos, Panayiotis J; Savvidou, Olga D; Korres, Demetrios S (J Long Term Eff Med Implants, 2009)
We present the clinical and radiographic outcomes of the cementless low-contact-stress (LCS) rotating-platform total knee arthroplasty. Overall, 423 prostheses were implanted in 393 consecutive patients (30 patients had bilateral total knee replacement) for primary varus gonarthrosis (381 patients) and rheumatoid arthritis (12 patients). There were 81 men and 312 women with a mean age of 73 years (range, 58-85 years). Patella replacement was not performed in any case. Clinical and radiographic evaluation was performed using the Knee Society Score (KSS) and the Knee Society Assessment Form, respectively. The mean follow-up was 10 years (range, 5-15 years). Three patients were lost to follow-up. Survival of the prostheses was 98% at 10 years; three prostheses required revision for deep infection, bearing dislocation, and periprosthetic fracture. The mean KSS improved significantly, from 42 and 44 points preoperatively to 90 and 79 points, respectively, at the latest evaluation (P < 0.001); results were excellent in 278 cases, good in 106, fair in 27, and poor in nine. Radiolucent lines were observed in 80 cases; revision arthroplasty was not performed in any of these cases. Complications included deep infection in one patient, bearing dislocation in one, skin necrosis in four, and a supracondylar fracture in one. The cementless LCS rotating-platform total knee arthroplasty is associated with excellent mid- and long-term results for patients with osteoarthritis and rheumatoid arthritis of the knee.
Keywords: Aged; Aged, 80 and over; Arthroplasty, Replacement, Knee; Female; Follow-Up Studies; Humans; Knee Prosthesis; Male; Middle Aged; Postoperative Complications; Prosthesis Design; Reoperation